Development of fish-based rice porridge using single-screw extruder / Noor Suhaina Abd Azis - Abd Azis, Noor Suhaina (2006)
This work was carried out to develop extrudate porridge using a single-screw extruder. The extrudate porridge developed had the texture similar with normal instant rice porridge in market, however extrudate porridge required 5 minutes to serve by heating in microwave oven on medium high level. Rice was used to produce porridge due to availability, price and suitable for children as well as adult people. Low value fish, Carangidae, Decapteius macroscoma, shortfin scads were used in this study, and was processed to dried powder, cooked and hydrolysed form to be used in extruder with coarse rice powder. Preliminary study had been done to produce plain rice porridge using traditional method. Long-grain rice was mixed with broken rice at ratio of 0:100, 25:75, 50:50:75:25, and 100:0 respectively. Each mixture was mixed to produce plain rice porridge. The physical and sensory properties of the each mixture were evaluated. The results obtained showed that plain rice porridge was best prepared using 100% long-grain rice. Physical characteristics of the plain rice porridge were relatively unchanged with the substitution of long-grain rice with broken rice. Studies had been done to produce direct expanded product using single-screw extruder. The powder mixture was extruded through a single-screw extruder, and the extrudate was cut manually using a scissor or knife as they came out the die to ensure similar pellets size, dried in oven at 60-66°C overnight to moisture content of 5-10% to maintain the shelf life of the product, and degree of expansion, solid density, colour, Water absorption index (WAI) and water solubility index (WSI) were measured. Water absorption and solubility indices of the extrudate were affected by feed moisture. Water absorption index increased significantly with increasing moisture content. However, WSI decreased, while WAI and solid density increased, when percentage of fish content increased. Expansion ratio, measured as area expansion, decreased as the percentage of fish content increased in feed mixture.